Stimulus-dependent representational drift in primary visual cortex - Tyler D. Marks (Nature Portfolio, 2021)
Here, the authors find that representational drift in visual cortex differs depending on the sensory stimulus, suggesting that the stability of neuronal responses is not a fixed property of individual cells, but rather depends on the encoded information.